Вы находитесь на странице: 1из 2

SPLBE - STATE OF KUWAIT QUADRATIC EQUATION

ALGEBRA – I Ax 2 +Bx+C = 0
Basic Fundamentals of Algebra

LAW OF ALGEBRA QUADRATIC FORMULA

1. Commutative Law of Addition – x+y = y+x −b ± √b 2 − 4ac


x=
2. Commutative Law of Multiplication x.y = y.x 2a
3. Associative Law of Addition – (x+y)+z = x+(y+z)
4. Associative Law of Multiplication – (x.y)z = x(y.z)
5. Distributive Property of Multiplication – x(y+z) = xy+xz Nature of roots:

The discriminant, B 2 − 4AC determines the nature of the roots of a


PROPERTIES OF FRACTION
quadratic equation.
A C A+C
Addition: + = When B 2 − 4AC = 0, roots are real an equal (one root only)
B B B
A C A−C
Subtraction: − = When B 2 − 4AC > 0, roots are real and unequal
B B B
A C AD BC AD+BC
Addition in different denominator: + = + = When B 2 − 4AC < 0, roots are imaginary and unequal
B D BD BD BD
A C AD BC AD−BC
Subtraction in different denominator: − = − =
B D BD BD BD Properties of roots:
A C AC
Multiplication: x =
B D BD
A C A D AD Let r1 and r2 be the roots of quadratic equation.
Division: ÷ = x =
B D B C BC
−B
When the two roots are added: r1 + r2 =
A
PROPERTIES OF EXPONENT PROPERTIES OF RADICALS
C
When the two roots are multiplied: r1. r2 =
A

Example. If 1/3 and -3/2 are the roots of quadratic equation, then the equation is?

A. 6x 2 +7x-3=0
B. 6x 2 -7x+3=0
C. 6x 2 -7x-3=0
D. 6x 2 -7x+1=0

THE REMAINDER THEOREM

If a polynomial in an unknown quantity x is divided by a first degree expression in


the same variable, (x-k), where k may be any real or complex number, the
remainder to be expected will be equal to the sum obtained when the numerical
value of k is substituted for x in the polynomial. Thus,

Remainder = f(x)
x→k
Example. Find the remainder if we divide 4x 2 +18x 2 +8y – 4 by (2y+3).

A. 10 C. 15
B. 11 D. 13

BINOMIAL THEOREM

The r th term of the binomial expansion of (x + y)n may be calculated using the
following formula:

r th term= n Cr−1 x
(n−r+1) (r−1)
y

Sum of the coefficients of expansion (x + y)n :

Sum = (Coeff. Of x + coeff. Of y)n

Sum of exponent of the expansion (x + y)n :

Sum = n(n+1)
1
Example: Find the 5th term of the expansion of (x 2 + )10 .
x

A. 260x 8 C. 210x 8
B. 5040x 8 D. 420x 8

What is the sum of the coefficients of the expansion of (2x − 1)20

A. 0 C. 2
B. 1 D. 3